Central venous catheter-related complications in critically ill children (2014)
Objective Placing central venous catheters is essential when managing critically ill children. This paper was thus aimed at identifying the major complications involved in this and determining the incidence of mechanical and infection-related complications associated with central venous catheterization in critically ill children. Material and Methods A descriptive study was undertaken between October 2011 and March 2012 of all new central venous catheters inserted in critically ill children. The definition of central venous catheter infection was based on CDC criteria. Results During the study period 200 central venous catheters were placed, 51 % in male patients, mostly infants; 71 % required mechanical ventilation and 56.5 % medication for hemodynamic support. Respiratory tract infections were the leading diagnosis on admission in 33 % of the cases. Complications were reported in 8.5 % of the children (52 % of these being due to mechanical complication and 48 % to infection). Mechanical complication incidence was 4.5% and eight central venous catheters fulfilled CDC criteria for central line associated blood stream infection (4 % incidence, i.e. 5 per 1,000 catheter/day rate). Conclusions Despite some complications arising from its use, central venous catheter placement is a safe procedure. Mechanical and infection incidence associated with central venous catheter placement should be known, not only because it differs from that regarding adult patients but also because this can help to establish preventative measures for reducing such complications and improving the care of critically ill children.